2023
DOI: 10.1590/1981-6723.01323
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical changes during controlled laboratory fermentation of cocoa (CCN-51) with the inclusion of fruits and on-farm inoculation

María Alicia Peña González,
Jennifer Pamela Ortiz Urgiles,
Fernanda Alegría Santander Pérez
et al.

Abstract: Fermentation is key to developing the organoleptic characteristics of cocoa beans, as dynamic changes in metabolites have a significant impact on flavors and aromas, hence modifications of this process have been investigated. In this research, the mucilage of CCN-51 cocoa beans was replaced by a mixture of passion fruit (Passiflora edulis) and plantain (Musa paradisiaca L.) pulp, and a controlled fermentation of this mixture was carried out after its spontaneous on-farm inoculation. The physicochemical changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Despite the differences in cacao species, the sugar content of FEC2 and CCN‐51 CME samples are similar. In contrast, Peña Gonzáles and colleagues (2023) reported lower fructose (21.91 g L −1 ) and glucose (24.75 g L −1 ) concentrations in cacao mucilage from Brazilian cacao.…”
Section: Resultsmentioning
confidence: 86%
“…Despite the differences in cacao species, the sugar content of FEC2 and CCN‐51 CME samples are similar. In contrast, Peña Gonzáles and colleagues (2023) reported lower fructose (21.91 g L −1 ) and glucose (24.75 g L −1 ) concentrations in cacao mucilage from Brazilian cacao.…”
Section: Resultsmentioning
confidence: 86%
“…It was observed that from the fifth day of fermentation the temperature did not vary, reaching a temperature between 40-50 °C, a desirable range for good fermentation [39]. On the other hand, from the third day of fermentation the mass recorded an increase in pH, a situation attributed to the decrease by leaching of citric acid contained in the pulp [40] and the decrease of volatile organic acids leading to an increase in pH in the fermentation mass [41] as to the metabolization of citric acid by the yeasts [42]. This decrease in pH within the first few days at all sites is attributed mainly to the diffusion of organic acids in the bean produced by lactic acid bacteria [43] and together with the high temperatures, which lead to embryo death, triggering a series of biochemical changes that greatly impact the development of bean flavor and color.…”
Section: Temperature and Ph Of Fermented Cocoa Beansmentioning
confidence: 97%